2022
DOI: 10.1136/jitc-2022-004712
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the CD47/thrombospondin-1 signaling axis regulates immune cell bioenergetics in the tumor microenvironment to potentiate antitumor immune response

Abstract: BackgroundCD47 is an integral membrane protein that alters adaptive immunosurveillance when bound to the matricellular glycoprotein thrombospondin-1 (TSP1). We examined the impact of the CD47/TSP1 signaling axis on melanoma patient response to anti-PD-1 therapy due to alterations in T cell activation, proliferation, effector function, and bioenergetics.MethodsA syngeneic B16 mouse melanoma model was performed to determine if targeting CD47 as monotherapy or in combination with anti-PD-1 impacted tumor burden. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…However, recent observations increasingly pointed to the role of CD47 targeting on TME, e.g. T eff cells 37,[53][54][55][56] . With regard to the potential CD47 targeting MOAs of HX009, the anti-lymphoma effect could be attributed to targeting to CD47 either on tumor cells or on T eff CD47 (or even other immune cells in TME), or on both.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent observations increasingly pointed to the role of CD47 targeting on TME, e.g. T eff cells 37,[53][54][55][56] . With regard to the potential CD47 targeting MOAs of HX009, the anti-lymphoma effect could be attributed to targeting to CD47 either on tumor cells or on T eff CD47 (or even other immune cells in TME), or on both.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CD47 overexpression in the TME allows tumour cells to avoid immune surveillance. Blocking T‐cell CD47 expression stimulates a sustained increase in Teff glycolytic efficiency and reestablishes the classical cytotoxic phenotype 180 . Moreover, clinical trials have demonstrated that a combination of CD47 mAbs and ICIs results in a reduced tumour burden and prolonged survival 181 .…”
Section: Therapeutic Advances In Targeting T‐cell Metabolic Processesmentioning
confidence: 99%
“…Furthermore, CD47 interacts with TSP-1, an extracellular matrix protein expressed in the TME [44]. TSP 1 exerts inhibitory effects on angiogenesis through multiple mechanisms, including the stimulation of endothelial cell apoptosis, inhibition of endothelial cell migration and proliferation, and regulation of vascular endothelial growth factor (VEGF) bioavailability and activity [45].…”
Section: Cd47 Function In the Tme And Signaling Pathwaysmentioning
confidence: 99%
“…CD47-mediated signaling between cancer and stromal cells CD47-mediated signaling plays a critical role in regulating tumor growth and progression by facilitating communication between cancer cells and stromal cells in the TME. It interacts with TSP-1, which is expressed on stromal cells such as endothelial cells and fibroblasts in the TME [44]. This interaction can potentially influence downstream signaling events that involve Akt/mTOR and NF-κB pathways, which promote tumor cell survival, invasion, and angiogenesis while inhibiting immune cell function.…”
Section: Regulation Of Immune Cell Infiltration By Cd47 In the Tmementioning
confidence: 99%